2012
DOI: 10.5588/ijtld.12.0074
|View full text |Cite
|
Sign up to set email alerts
|

An evaluation of ‘Ribolola’: a household tuberculosis contact tracing programme in North West Province, South Africa

Abstract: SUMMARY SettingRural/periurban community, South Africa. ObjectivesTo examine the yield of tuberculosis (TB) cases, TB preventive therapy (TBPT) initiation and human immunodeficiency virus (HIV) diagnoses from household TB contact tracing. DesignRetrospective programme analysis. MethodsHouseholds of index TB cases were visited and their contacts screened for TB and HIV. TB suspects provided sputum or were referred for assessment. Contacts aged <5 years were referred for assessment for TBPT initiation. Conclusi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
19
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 9 publications
2
19
0
Order By: Relevance
“…We also observed poor performance of sputum fluorescence microscopy to identify TB disease: only 1 of 35 TB cases was positive by smear microscopy. Poor performance of smear microscopy has also been reported from other ICF programs [29], [30].…”
Section: Discussionmentioning
confidence: 52%
“…We also observed poor performance of sputum fluorescence microscopy to identify TB disease: only 1 of 35 TB cases was positive by smear microscopy. Poor performance of smear microscopy has also been reported from other ICF programs [29], [30].…”
Section: Discussionmentioning
confidence: 52%
“…6 The low proportion of contacts from whom we were able to collect a sputum sample and our deliberately pragmatic design may, in part, explain the lower yield in our study compared to two other South African studies. We used lay health workers instead of nurses, 6 made only one household visit attempt instead of up to three, 6,16 collected a single spontaneous sputum rather than one spot and two early morning sputum samples 16 or induced sputum, 6 and did not perform culture. 6,16 …”
Section: Discussionmentioning
confidence: 99%
“…Other models from the literature have shown much higher yields, although with a signifi cant increase in resources. 6,7 While the enhanced models presented here were not effective at detecting undiagnosed TB cases, there were a number of operational issues that may have impacted on their effectiveness. The lessons learnt and the practical challenges demonstrated are relevant for those working to implement services in similar settings.…”
Section: Discussionmentioning
confidence: 99%
“…5 Two South African studies in which contacts were screened in their homes found a high yield of TB of between 3% and 9%. 6,7 However, these programmes can be costly, and intensive interventions operating in parallel to existing services may not be sustainable. 8 The Stop TB Partnership advises that contact screening should be managed within existing programmes by establishing a 'contact clinic' at the health centre.…”
mentioning
confidence: 99%